Egyptian stories - Hull, Robert (Hove Wayland, 1993)
"Egyptian Stories" by Robert Hull, published in 1993. This 48-page hardcover book is part of the "Tales from Around the World" series and offers a collection of Egyptian traditional myths and stories, illustrated in both color and black-and-white The narratives include tales such as "The Murder of Osiris," "King Solomon and the Burning Sun," and "The First Light." Given its publication date, the book provides historical context up to the early 1990s. For more recent information on Egyptian stories, additional sources would be beneficial.